Peran Pendidikan Agama Islam Dalam Membangun Moralitas Siswa Di Era Digital - Abdul Latif (Sipakatau: Jurnal Pendidikan dan Kebudayaan, 2026)
This study aims to analyze the role of Islamic Religious Education in building students’ morality in the digital era. While digital technology offers numerous benefits, it also poses serious challenges to students’ moral development, particularly in terms of ethical behavior, social interaction, and self-control. This research employs a qualitative approach using a library research design by analyzing data from academic books, scholarly journal articles, and normative Islamic sources, namely the Qur’an and Hadith, relevant to morality and education. The findings indicate that Islamic Religious Education plays a strategic role in shaping students’ morality through the internalization of Islamic moral values, the strengthening of religious character, and the development of digital ethics based on Islamic teachings. Islamic Religious Education functions as a foundation of values, a means of moral control, and a filter against negative influences in the digital era. The effectiveness of this role depends on the application of contextual learning strategies, the exemplary conduct of educators, and the habituation of religious values within the educational environment. Therefore, Islamic Religious Education is an essential instrument in developing students who are faithful, possess noble character, and are responsible in utilizing digital technology.